Mechano-catalytic conversion of polypropylene over zeolite-based materials - Hergesell, Adrian H; Seitzinger, Claire L; Pasternak, Hubert; Seidling, Laura; Ospina Guarin, Viviana M; Karpensky, Nicole; Puch, Florian; Welzel, Thomas; Vollmer, Ina (Catalysis science & technology, 2025)
Chemical recycling can convert polymers into useful chemicals. Polyolefins can be chemically recycled into their monomers and other hydrocarbons catalytic pyrolysis or mechano-chemistry. While pyrolysis catalysts are highly active but not selective, mechano-chemistry is more selective but lacks quantitative yields. To address these issues and unlock potential synergies, we herein investigate the effect of zeolite-based pyrolysis catalysts on the conversion of polypropylene during ball milling at room temperature and elevated temperatures, as well as during catalytic kneading. Initially, zeolite catalysts are highly active in the ball mill and their activity is dependent on acid site density. However, they deactivate quickly under the harsh collisions in the ball mill due to the collapse of their crystalline framework. To circumvent deactivation, we used the concept of direct mechano-catalysis and immobilized the zeolite material on surface-roughened grinding spheres. This effectively protects active sites against contact with the container wall or other grinding spheres while allowing contact with polypropylene, leading to sustained catalytic activity and requiring much lower amounts of zeolite. In addition, catalytic kneading of molten polypropylene was investigated as an alternative where energy input is more uniformly distributed in the volume and time compared to highly localized and forceful impacts within the ball mill. Although a synergy of thermo- and mechano-chemical effects was observed initially, the energy intake was limited by a fast decline of melt viscosity due to polymer backbone cleavage. Mechano-chemical conversion and catalytic pyrolysis of polyolefins are two promising platforms for chemical recycling. Our study illustrates the difficulties in combining both and possible pathways to overcome these challenges.